2003
DOI: 10.2214/ajr.181.3.1810663
|View full text |Cite
|
Sign up to set email alerts
|

Gadobenate Dimeglumine-Enhanced MRI of the Breast:Analysis of Dose Response and Comparison with Gadopentetate Dimeglumine

Abstract: Gadobenate dimeglumine is a capable diagnostic agent for MRI of the breast. Although preliminary, our results suggest that 0.1 mmol/kg of gadobenate dimeglumine may offer advantages over doses of 0.05 and 0.2 mmol/kg of gadobenate dimeglumine and 0.1 mmol/kg of gadopentetate dimeglumine for breast lesion detection and characterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 40 publications
3
51
1
7
Order By: Relevance
“…Secondly, due to the rapidly evolving developments of MRI technology, further reductions in equipment costs are likely to result in lower equipment costs per screening examination. Thirdly, there are likely to be cost reductions with regard to the contrast medium: a lower dose (0.1 mmol kg À1 body weight) of Gd-DTPA has been shown to be similarly effective (Knopp et al, 2003) compared to 0.2 mmol kg À1 used in our study and in addition, the expected availability of a generic formulation. Further cost reductions can be expected due to the increasing experience of radiologists with this new technique, resulting in a reduction of recalled cases as shown in a recent report ).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Secondly, due to the rapidly evolving developments of MRI technology, further reductions in equipment costs are likely to result in lower equipment costs per screening examination. Thirdly, there are likely to be cost reductions with regard to the contrast medium: a lower dose (0.1 mmol kg À1 body weight) of Gd-DTPA has been shown to be similarly effective (Knopp et al, 2003) compared to 0.2 mmol kg À1 used in our study and in addition, the expected availability of a generic formulation. Further cost reductions can be expected due to the increasing experience of radiologists with this new technique, resulting in a reduction of recalled cases as shown in a recent report ).…”
Section: Discussionmentioning
confidence: 85%
“…Improved CE MRI protocols for routine clinical practice will require less time for the MRI examination and subsequent analysis than dictated by the research protocol, which was designed to collect additional information to determine which features of a range of potential measurements provided the most sensitive and specific assessment of breast cancer (Brown et al, 2000b). Other cost reducing factors in routine practice are lower MRI equipment costs (compared with the highly specified systems purchased by research centres), more experienced radiologists working in breast CE MRI and the possible introduction of generic formulations of Gd-DTPA coupled with potential lower dose than o0.2 mmol per kg (Knopp et al, 2003). We therefore estimated alternative unit cost based on the following assumptions:…”
Section: Unit Costmentioning
confidence: 99%
“…We excluded lesions that were smaller than 0.7 cm (7), cystic lesions (4), lesions for which we did not obtain pathology (11), and one lesion because the patient moved during the exam. Two of the seven lesions that were smaller than 0.7 cm were malignant at pathology and demonstrated a high signal on DWI.…”
Section: Resultsmentioning
confidence: 99%
“…No significant differences were observed between the two contrast agents in terms of lesion detection, Breast Imaging-Reporting and Data System assessment or lesion enhancement and morphology and the authors concluded that gadobutrol is non-inferior to gadobenate dimeglumine for breast cancer staging. 33 However, unlike the comparisons of gadobenate dimeglumine and gadopentetate dimeglumine [22][23][24][25][26] this study was open to criticism in terms of the patient inclusion criteria and the manner in which the study end-points were selected and analyzed. …”
Section: Unique Features Of Gadobenate Dimeglumine For Breast Mrimentioning
confidence: 99%
“…[22][23][24][25][26] An early study to establish the optimal dose of gadobenate dimeglumine to use for breast MRI established that 0.1 mmol/kg of bodyweight is superior to doses of 0.05 and 0.2 mmol/kg of bodyweight in terms of lesion detection in women with known or suspected breast cancer. 22 Furthermore, 0.1 mmol/kg gadobenate dimeglumine was also shown to be significantly superior to an equivalent dose of gadopentetate dimeglumine, not only in terms of malignant lesion detection but also for quantitative contrast enhancement and sensitivity for lesion characterization, meaning that detected lesions were easier to see and classify. Importantly, fewer false positive determinations were made with 0.1 mmol/kg gadobenate dimeglumine than with 0.1 mmol/kg gadopentetate dimeglumine.…”
Section: Gadobenate Dimeglumine (Multihance) In Breast Mrimentioning
confidence: 99%